An In vitro Comparison of pushout bond strength of resilon with MetaSEAL and AH plus sealers - Priyanka Sarangi; Rashmirekha Mallick; Sukanta Kumar Satapathy; Gaurav Sharma; Fathima Kouser; Satyajit Mohapatra (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study is to evaluate and compare the pushout bond strengths of Resilon with two different sealers: Resilon/MetaSEAL (methacrylate based) and Resilon/AH Plus (an epoxy resin-based sealer). Materials and Methods: Forty single canal anterior teeth were decoronated at cementoenamel junction and standardized to 10 ± 1 mm length. Working length was determined followed by biomechanical preparation. Then, the specimens were randomly assigned into two groups of 20 teeth each based on the sealer used with Resilon. All canals were obturated using single-cone obturation technique. Root samples were prepared for pushout testing. The universal testing machine gave the debonding force for individual specimen. This was done for all the specimens. Statistical Analysis: This was done by using unpaired Student's t- test. Results: The roots filled with Resilon/MetaSEAL had higher bond strength (1.49 ± 0.09 MPa) compared to Resilon/AH Plus (0.90 ± 0.04 MPa) group. The difference in bond strength was statistically significant (P = 0.0000). Conclusion: Through this pushout bond strength test, it could be noted that MetaSEAL did appear to bond to the dentin and could be used as a potential endodontic sealer.